A method for non-invasive retrieval of membranes for flow batteries using electrolysis technology

CN122930946APending Publication Date: 2026-10-16INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510423570.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对现有技术传统机械剥离法带来的产品残次率高,膜结构损伤的问题,本发明提供一种利用电解技术无损伤揭取液流电池用隔膜的方法,采用电化学取膜法通过电解,在膜-基底界面生成气体(如H2或O2),利用气泡的物理分离作用或基底电解腐蚀实现非接触式剥离,有效避免了机械损伤,完整保留隔膜的微观结构(如孔隙率、厚度均匀性),降低产品的残次率

Benefits of technology

1、本发明提出的电化学取膜法通过电解反应在基底与隔膜界面生成气体(如H2或O2),利用气泡的物理分离作用或基底可控腐蚀实现非接触式剥离。此过程避免了传统机械剥离中因外力作用导致的隔膜撕裂、划痕或结构损伤,尤其适用于超薄、柔性或复杂结构的隔膜。隔膜的微观特性(如孔隙率、厚度均匀性)得以完整保留,确保其离子选择性与导电性不受损伤。同时,电解剥离避免了工具接触带来的表面污染,进一步提升隔膜在液流电池中的传输效率与长期稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930946A_ABST
    Figure CN122930946A_ABST
Patent Text Reader

Abstract

The application relates to the field of liquid flow battery diaphragm, in particular to a method for non-damage stripping of liquid flow battery diaphragm by using electrolysis technology; first, the liquid flow battery diaphragm is prepared on the surface of a conductive base, and after the film preparation process is completed, the base is put into an acid or alkaline solution for electrolysis together with the liquid flow battery diaphragm. The process generates small bubbles between the base and the film, significantly reduces the adhesion between the film and the base, or completely electrolytic corrosion of the base, and the liquid flow battery diaphragm is non-damage taken down. The application has the advantages of simple process, effective avoidance of damage to the film structure in the film taking process, and reduction of the defective rate of the film. The prepared diaphragm has good ion selectivity, mechanical properties and good conductivity, so that the liquid flow battery has good battery performance, and the application provides a new idea for the development of the liquid flow battery diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flow battery separator manufacturing, specifically a method for non-destructive removal of flow battery separators using electrolysis technology. Background Technology

[0002] Wind, solar, and biomass energy, as major renewable energy sources, are clean and abundant, and have received widespread attention. However, these energy sources originate from nature and are intermittent, resulting in unstable power generation capacity and a contradiction between seasonal, unstable power generation and the continuous and stable demand for electricity. In response to this situation, developing effective energy storage technologies to ensure the stability of power supply has become crucial for the widespread application of renewable energy.

[0003] Flow redox batteries (RFBs), as an advanced energy storage technology, have become an important solution to energy storage problems due to their unique structure and excellent performance, offering high energy density, long cycle life, and superior safety. The separator is the core component of a flow battery, its main function being to prevent the mixing of the positive and negative electrode solutions while allowing ions to migrate freely within the battery, thus completing the current flow and energy conversion. The performance of the separator directly affects the overall efficiency and stability of the battery. An ideal separator not only needs excellent mechanical strength and chemical stability but also must achieve an effective balance between proton conductivity and ion selectivity. This balance determines the diffusion and selective conduction capabilities of active ions, thereby affecting the battery's energy efficiency and power density.

[0004] In membrane fabrication, peeling the membrane from the substrate is usually the final step. Traditional mechanical peeling uses a scraper and relies on external force to directly separate the membrane from the substrate. This method is prone to stress concentration, leading to membrane tearing, scratches, or structural damage, especially for ultrathin and flexible membranes. Electrochemical membrane peeling, on the other hand, generates gas (such as H2 or O2) at the membrane-substrate interface through electrolysis. The physical separation effect of the bubbles or electrolytic corrosion of the substrate achieves non-contact peeling, effectively avoiding mechanical damage, preserving the membrane's microstructure (such as porosity and thickness uniformity), and reducing product defects.

[0005] Meanwhile, the process parameters (current density, electrolyte pH, etc.) of the electrochemical membrane extraction method can be precisely controlled, adapting to different substrate materials (metal, carbon-based) and complex membrane structures. Furthermore, the membrane surface obtained by this method is pollution-free and has a certain probability of forming an active layer due to substrate electrolysis, further optimizing the ion selectivity and conductivity of the membrane. This provides an efficient and environmentally friendly solution for the large-scale production of high-performance flow battery membranes. Summary of the Invention

[0006] To address the issues of high defect rates and membrane structure damage associated with traditional mechanical peeling methods, this invention provides a non-destructive method for peeling separators used in flow batteries using electrolysis. This electrochemical peeling method generates gas (such as H2 or O2) at the membrane-substrate interface through electrolysis. The physical separation effect of the gas bubbles or electrolytic corrosion of the substrate achieves non-contact peeling, effectively avoiding mechanical damage and preserving the separator's microstructure (such as porosity and thickness uniformity), thus reducing the defect rate. Furthermore, the process parameters (current density, electrolyte pH, etc.) of the electrochemical peeling method can be precisely controlled to adapt to different substrate materials (metal, carbon-based) and complex separator structures. In addition, the peeled separator surface is free of contamination and has a certain probability of forming an active layer due to substrate electrolysis, further optimizing the separator's ion selectivity and conductivity. This provides an efficient and environmentally friendly solution for the large-scale production of high-performance flow battery separators.

[0007] The technical solution of this invention is: A method for non-destructively peeling off the separator of a flow battery using electrolysis technology includes the following steps: Step (1): Dissolve the film-forming resin in an organic solvent to prepare a film-forming resin solution with a mass percentage of 1-75%. Prepare a flow battery separator on a conductive substrate by casting, extrusion or electrochemical deposition to form a film-substrate composite structure. Step (2): Add acidic or alkaline electrolyte to the modular or continuous membrane electrolysis cell; Step (3): Take out the membrane-substrate composite structure from step (1), ensuring that the membrane surface is undamaged, and immerse it in the electrolyte described in step (2); Step (4): A counter electrode is placed above or below the membrane-substrate composite structure in step (3), and the counter electrode is completely immersed in the electrolyte; Step (5): Apply current to the membrane-substrate composite structure and the counter electrode in step (4) to carry out the electrolysis process. Stir the electrolyte during electrolysis until sufficient small bubbles are generated between the membrane and the substrate or the substrate is completely corroded. Step (6): If the substrate in step (5) is not completely corroded but there are enough small bubbles between the membrane and the substrate, the membrane-substrate composite structure is removed, the membrane edge is peeled off and the interface is rinsed to separate the membrane. Specifically, a small part of the membrane at the edge of the membrane-substrate is peeled off first, the interface between the membrane and the substrate is rinsed with running water until the membrane is separated from the substrate, and then the membrane is collected by a membrane collection device and processed for subsequent treatment. If the substrate in step (5) is completely corroded, the membrane is collected directly by a membrane collection device and processed for subsequent treatment. If the number of small bubbles generated between the membrane and the substrate is insufficient, or the substrate is not completely corroded, resulting in insufficient peeling, the electrolysis is repeated to extend the electrolysis time.

[0008] Furthermore, in the above-mentioned method for non-destructively peeling off the separator for a flow battery using electrolysis technology, in step (1), the film-forming resin is one or more of the following: perfluorosulfonic acid resin, sulfonated polyether ether ketone, polybenzothiazole, polybenzimidazole, sulfonated polyethylene, polyether sulfone, sulfonated polypropylene, polyimide, polysulfone, polyether ether ketone, perfluorocarboxylic acid resin, polyvinylidene fluoride resin, polypropylene, polyethylene, and polyvinylidene fluoride; and the organic solvent is selected from one or more of the following: dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, or dichloromethane.

[0009] Furthermore, in the above-mentioned method for non-destructively removing the separator for a flow battery using electrolysis technology, in step (1), the conductive substrate is one of the following: boron-doped diamond film, titanium-based ruthenium-iridium plate or foil, titanium-based iridium-tantalum plate or foil, titanium-based ruthenium-indium-tin plate or foil, titanium-based tin-antimony oxide plate or foil, titanium-based titanium suboxide plate or foil, and titanium-based lead dioxide plate or foil; at least one of the following metal material plates or foils: stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, niobium, tantalum, zirconium, tungsten, cerium, aluminum, bismuth, rhenium, barium, osmium, tin, lead, gold, silver, platinum, palladium, iridium, rhodium, molybdenum, and ruthenium; or any one of the following carbon material plates or foils: graphite felt, carbon felt, graphite, glassy carbon, boron-doped diamond, activated carbon, graphene, carbon fiber, carbon nanotubes, and carbon sponge.

[0010] Furthermore, in the above-mentioned method for non-destructively removing the separator for a flow battery using electrolysis technology, in step (2), the concentration of the acidic electrolyte is 0.1-5 mol·L⁻¹. -1 This includes solutions of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, carbonic acid, hydrosulfuric acid, sulfurous acid, hydrofluoric acid, or citric acid; the alkaline electrolyte concentration is 0.1-5 mol·L⁻¹. -1 This includes solutions of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ammonia, calcium hydroxide, sodium phosphate, sodium sulfite, sodium sulfide, or sodium aluminate.

[0011] Furthermore, in the above-mentioned method for non-destructively removing the separator for a flow battery using electrolysis technology, in step (4), the electrode shape is sheet-like, rod-like, or foil-like, with a thickness of 5-100,000 μm. μm, the counter electrode shape is any one of sheet, rod, filament, granular, sponge, mesh and porous structure; the counter electrode material is one of boron-doped diamond film, titanium-based ruthenium-iridium plate or foil, titanium-based iridium-tantalum plate or foil, titanium-based ruthenium-indium-tin plate or foil, titanium-based tin-antimony oxide plate or foil, titanium-based titanium suboxide plate or foil and titanium-based lead dioxide plate or foil; at least one of stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, niobium, tantalum, zirconium, tungsten, cerium, aluminum, bismuth, rhenium, barium, osmium, tin, lead, gold, silver, platinum, palladium, iridium, rhodium, molybdenum and ruthenium metal material plate or foil; any one of graphite felt, carbon felt, graphite, glassy carbon, boron-doped diamond, activated carbon, graphene, carbon fiber, carbon nanotubes and carbon sponge carbon material plate or foil.

[0012] Furthermore, in the above-mentioned method of non-destructively peeling off the separator for a flow battery using electrolysis technology, in step (4), the area ratio of the membrane-substrate composite structure to the counter electrode is 1:10 to 10:1, and the spacing is 1 mm to 100 mm; the membrane-substrate composite structure serves as the positive or negative electrode, and the counter electrode serves as the corresponding negative or positive electrode.

[0013] Furthermore, in the above-mentioned method for non-destructively removing the separator for a flow battery using electrolysis technology, in step (5), when the electrolysis is performed in constant current mode, the current density range is 10 mA·cm⁻¹. -2 ~1000 mA·cm -2 The electrolysis time is 1–120 min, and the temperature is 25 ℃–70 ℃. In constant voltage mode, the voltage range is 1 V–150 V, the electrolysis time is 1–120 min, and the electrolysis temperature is 25 ℃–70 ℃. In constant current pulse mode, the current density range is 10 mA·cm⁻¹. -2 ~1000 mA·cm -2 The electrolysis time is 1–120 min, the frequency is 200–2000 Hz, the duty cycle is 20%–80%, and the electrolysis temperature is 25 ℃–70 ℃.

[0014] Furthermore, the aforementioned method for non-destructively removing the separator for flow batteries using electrolysis technology yields a separator with a thickness of 10–100 μm, a tensile strength greater than 20 MPa, an elongation at break greater than 90%, and an ionic conductivity greater than 12 mS·cm. -1 .

[0015] Furthermore, the above-mentioned method for non-destructively removing the separator for a flow battery using electrolysis technology is applicable to flow battery systems including any one or more of the following: iron-chromium, vanadium-based, zinc-iron, ferrous, zinc-bromine, sodium / bromine polysulfide, titanium-manganese, or organic flow batteries.

[0016] Furthermore, in the aforementioned method for non-destructive removal of the separator for a flow battery using electrolysis technology, the removed separator surface has no mechanical damage, and the vanadium ion permeability constant is less than 20 × 10⁻⁶. -7 cm·min, and at 200 mA·cm -2 The energy efficiency of the flow battery is greater than 75% at the current density.

[0017] The design concept of this invention is as follows: First, this invention dissolves a film-forming resin in an organic solvent to prepare a solution with a mass fraction of 1-75%. A uniform flow battery membrane is then fabricated on a conductive substrate surface using methods such as casting, extrusion, or electrochemical deposition. Subsequently, the membrane-substrate pair is immersed in an acidic or alkaline electrolyte, with a counter electrode positioned above or below it, ensuring complete immersion before electrolysis. During electrolysis, parameters such as current density, electrolyte pH, and stirring rate are adjusted to induce the generation of numerous small bubbles (e.g., H2 or O2) at the substrate-membrane interface, or to directly electrolyze and completely corrode the substrate. If sufficient bubbles are generated but the substrate is not completely corroded, non-destructive separation can be achieved by peeling off the membrane edges and rinsing the interface. If the substrate is completely corroded, the membrane can be collected directly. If peeling fails, the electrolysis time needs to be extended or the parameters optimized before repeating the process. This method achieves non-contact peeling through electrolysis, avoiding the damage to the microstructure of the separator, such as porosity, thickness, and uniformity, caused by mechanical stress. The electrolysis parameters are precisely controllable and adaptable to substrates of different materials (such as metals and carbon-based materials) and separators with complex structures. The resulting separator surface is free of contamination, exhibiting excellent ion selectivity and conductivity, providing a reliable process route for the large-scale production of high-performance flow batteries. Its technical specifications are as follows: electrolyte concentration 0.1-5 mol·L⁻¹ -1 pH range -1 to 15, membrane thickness 10 to 100 μm, tensile strength > 20 MPa, elongation at break > 90%, ionic conductivity > 12 mS·cm -1 Vanadium ion permeability constant < 20 × 10⁻⁶ -7 cm·min, flow cell 200 mA·cm -2 The energy efficiency of the flow battery at the current density is >75%, 150 mA·cm. -2 The energy efficiency of flow batteries at current densities is >80%, 100 mA·cm⁻¹. -2 The energy efficiency of the flow battery at the current density is >81%.

[0018] Advantages and beneficial effects of the present invention: 1. The electrochemical membrane stripping method proposed in this invention generates gas (such as H2 or O2) at the interface between the substrate and the membrane through an electrolytic reaction. Non-contact stripping is achieved by utilizing the physical separation effect of the bubbles or controlled corrosion of the substrate. This process avoids membrane tearing, scratching, or structural damage caused by external forces in traditional mechanical stripping, and is particularly suitable for ultra-thin, flexible, or complex membranes. The microscopic properties of the membrane (such as porosity and thickness uniformity) are fully preserved, ensuring that its ion selectivity and conductivity are not damaged. Simultaneously, electrolytic stripping avoids surface contamination caused by tool contact, further improving the membrane's transport efficiency and long-term stability in flow batteries.

[0019] 2. This method flexibly controls the stripping process by precisely adjusting electrolysis parameters (current density, electrolyte pH, and time), making it adaptable to various substrate materials such as metals and carbon-based materials, as well as complex separators with gradient pores and composite structures, significantly improving production yield. Furthermore, electrolytic stripping eliminates the need for high-precision mechanical devices, simplifying the process and making it suitable for roll-to-roll continuous production. This provides an efficient solution for the large-scale, low-cost manufacturing of high-performance flow battery separators. Attached Figure Description

[0020] Figure 1 Schematic diagram of a modular membrane electrolyzer; Figure 2 This is a schematic diagram of a continuous membrane electrolyzer. Detailed Implementation

[0021] In its specific implementation, this invention dissolves the film-forming resin in an organic solvent (1-75% concentration) and prepares a uniform diaphragm on the surface of a conductive substrate using methods such as casting, extrusion, or electrochemical deposition. Subsequently, the membrane-substrate is immersed in an acidic or alkaline electrolyte, with a counter electrode positioned above or below it. After energizing, the current density and stirring rate are adjusted to generate a large number of bubbles (such as H2 or O2) at the substrate-diaphragm interface, or the substrate is directly electrolytically corroded. If the substrate is not completely corroded but there are sufficient bubbles at the interface, the edge diaphragm can be peeled off and the interface rinsed to achieve non-destructive separation. If the substrate is completely corroded, the diaphragm is collected directly. If the membrane and substrate are tightly bonded and cannot be peeled off, the electrolysis time is extended. This method utilizes the non-contact peeling mechanism of the electrolytic reaction, avoiding the damage to the microstructure of the diaphragm, such as porosity and thickness uniformity, caused by mechanical stress. Simultaneously, electrolysis parameters (such as current and time) can be precisely controlled, adapting to various substrates such as metals and carbon-based membranes, as well as complex membrane structures. The resulting separator is free from surface contamination and possesses both excellent ion selectivity and conductivity, providing a reliable technical path for the efficient, environmentally friendly, and large-scale production of flow batteries.

[0022] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be used to limit the scope of the present invention. Example 1

[0023] Step (1): Dissolve perfluorosulfonic acid resin (PFSA) in N,N-dimethylformamide to prepare a homogeneous solution with a mass fraction of 10%, and then cast it onto a 10×10 cm substrate using the casting method. 2 A film is coated on the surface of a 0.1 mm thick titanium foil, and after drying at 140 ℃, a dense membrane with a thickness of about 50 μm is formed. Step (2), towards Figure 1 In the modular membrane electrolytic cell, a 0.5 M dilute sulfuric acid solution was added to the polytetrafluoroethylene electrolytic cell, and the solution temperature was controlled at 25 ± 2 ℃. Step (3): Slowly and vertically immerse the titanium foil substrate and PFSA membrane into the electrolyte to avoid wrinkles or scratches on the membrane surface. Step (4): Place a 10×10 cm membrane directly above the membrane-substrate. 2 The platinum sheet electrodes were adjusted to a spacing of 5 mm to ensure a uniform electric field distribution. Step (5): At room temperature, apply a constant current of 10 mA·cm⁻¹. -2 At the specified current density, the electrolyte was electrolyzed for 10 min while being magnetically stirred at 200 rpm. Dense H2 bubbles were observed continuously precipitated at the interface between the titanium substrate and the membrane, and the interfacial adhesion was significantly reduced. Step (6): After removing the membrane-substrate, gently peel off the edge of the membrane in a 5 mm area with a polytetrafluoroethylene scraper, rinse the interface with deionized water at a 30° angle for 10 s to completely separate the PFSA membrane from the titanium foil, and then continuously collect the membrane with a vacuum adsorption roller. Step (8): If there is insufficient bubble density in some areas of the titanium foil surface and residual adhesion between the film and the substrate, electrolysis needs to be repeated and the stirring rate increased to 300 rpm to finally achieve non-destructive peeling of the entire area.

[0024] In this embodiment, the obtained PFSA film has a thickness of 50 μm, a smooth and flat surface, and no structural defects. Its basic performance and performance in a vanadium redox flow battery were tested, and the results are shown in Table 1. Example 2

[0025] In this embodiment, the method for non-destructively removing the separator for the flow battery using electrolysis technology is as follows: Step (1): Dissolve polystyrene sulfonic acid (PSSA) powder in N,N-dimethylformamide (DMF) to prepare a 25% mass fraction viscous solution, and prepare a sulfonic acid functionalized membrane with a thickness of 80 μm on the surface of carbon cloth by electrochemical deposition. Step (2), towards Figure 2 1 M NaOH solution was injected into the continuous membrane electrolysis cell; Step (3): Immerse the carbon cloth substrate and PSSA diaphragm horizontally into the electrolyte to ensure complete wetting of the carbon fibers; Step (4): Fix the nickel mesh counter electrode (1 mm aperture) 10 mm below the film-substrate and fix its position with an insulating clamp; Step (5): Electrolyze at 40 °C in 5 V constant voltage mode for 15 min with ultrasonic-assisted stirring (40 kHz). The carbon cloth substrate is gradually corroded by the alkaline electrolyte, and the diaphragm is suspended in the solution. Step (7): Use a vacuum adsorption roller to continuously collect the film, directly collect the complete PSSA membrane, and wash with ethanol to remove residual alkali solution; Step (8): Because the carbon cloth substrate is thoroughly corroded, there is no need for repeated electrolysis.

[0026] In this embodiment, the obtained PSSA separator has a thickness of 80 μm, a smooth and flat surface, and no structural defects. Its basic performance and performance in a vanadium redox flow battery were tested, and the results are shown in Table 1. Example 3

[0027] In this embodiment, the method for non-destructively removing the separator for the flow battery using electrolysis technology is as follows: Step (1): Sulfonated polyether ether ketone (SPEEK) was dissolved in dimethyl sulfoxide to prepare a 40% mass fraction orange-red solution. The solution was then calendered onto a nickel foil substrate using a high-temperature (120°C) extruder. After washing and curing with water, a chemically resistant membrane with a thickness of 70 μm was obtained. Step (2), towards Figure 1 Phosphoric acid (H3PO4) solution was added to the modular peelable membrane electrolyzer, and the pH value was adjusted to 2.5; Step (3): The nickel foil substrate and SPEEK membrane are slowly immersed in the electrolyte to reduce bubble retention; Step (4): Fix the graphite plate counter electrode 10 mm above the membrane-substrate, with the electrode area matching the substrate; Step (5): At 35 °C, at 15 mA·cm -2 Constant current pulse electrolysis for 8 min, while the electrolyte was stirred at 150 rpm using a paddle stirrer. H2 bubbles were observed to be generated at the interface between the nickel foil substrate and the SPEEK membrane, but the substrate was only slightly corroded. Step (6): Gently scrape a 1 cm area at the edge of the diaphragm with a Teflon scraper, and then rinse the interface with a deionized water jet (pressure 0.2 MPa) for 30 s to completely detach the SPEEK membrane from the nickel foil substrate. Step (8): If there is insufficient bubble density in some areas of the nickel foil surface and residual adhesion between the film and the substrate, electrolysis needs to be repeated to finally achieve non-destructive peeling of the entire area.

[0028] In this embodiment, the obtained SPEEK film has a thickness of 70 μm, a smooth and flat surface, and no structural defects. Its basic performance and performance in a vanadium redox flow battery were tested, and the results are shown in Table 1. Example 4

[0029] In this embodiment, the method for non-destructively removing the separator for the flow battery using electrolysis technology is as follows: Step (1): Dissolve polybenzothiazole resin in N-methylpyrrolidone (NMP) and form a high-strength membrane with a thickness of 75 μm on the surface of a polished graphite plate by casting. Step (2), towards Figure 2 A 2 M nitric acid (HNO3) solution was injected into the continuous peeling membrane electrolyzer and pre-cooled to 5 °C to suppress side reactions; Step (3): Immerse the graphite substrate and the polybenzothiazole membrane in the electrolyte to ensure that the membrane surface is in complete contact with the solution; Step (4): Install a titanium plate counter electrode (2 mm thick) 20 mm above the membrane-substrate and fix the spacing with a polypropylene bracket; Step (5): At 5 °C, at 20 mA·cm 2 Electrolysis at current density for 15 min, combined with eddy current stirring (500 rpm), causes the graphite substrate to corrode in the electrolyte, allowing the diaphragm to be completely removed; Step (7): Use a vacuum adsorption roller to continuously collect the film, directly collect the complete polybenzothiazole membrane, and wash it with deionized water to remove residual acid. Step (8): Due to graphite oxidation and corrosion, the stripping process is completed in one go and does not need to be repeated. In this embodiment, the obtained polybenzothiazole film has a thickness of 75 μm, a smooth and flat surface, and no structural defects. The basic performance of Examples 1-4 and their performance in vanadium redox flow batteries were tested, and the results are shown in Table 1.

[0030] Table 1. Results of diaphragm performance tests in cases 1-4 project Tensile strength Elongation at break Ion conductivity Vanadium ion permeability constant <![CDATA[200 mA cm −2 Vanadium redox flow battery energy efficiency <![CDATA[150 mA cm −2 Energy efficiency of iron-chromium redox flow batteries <![CDATA[100 mA cm −2 Energy efficiency of titanium-manganese redox flow batteries unit MPa % <![CDATA[mS cm -1 ]]> <![CDATA[×10 -7 cm min -1 ]]> % % % Preparation of perfluorosulfonic acid membranes by casting method 25.4 110.2 11.5 30.3 75.32 78.32 77.32 Example 1 34.75 102.42 16.45 15.32 76.32 80.32 81.32 Example 2 27.45 98.33 14.17 13.26 78.32 80.32 82.32 Example 3 33.92 102.34 15.23 15.32 78.14 80.14 83.14 Example 4 34.81 99.6 14.29 12.98 78.45 80.45 81.45 The results of the embodiments show that the separators for flow batteries obtained by the non-destructive electrolytic stripping method of the present invention exhibit good mechanical properties, and the internal structure of the membrane remains undamaged. Simultaneously, electrolytic stripping avoids surface contamination caused by tool contact and also improves the membrane's vanadium-blocking performance, conductivity, and battery performance. Furthermore, this method is simple to operate, effectively reduces the defect rate in the membrane production process, and can be widely applied in the field of flow batteries.

Claims

1. A method for non-destructively peeling off the separator of a flow battery using electrolysis technology, characterized in that, Includes the following steps: Step (1): Dissolve the film-forming resin in an organic solvent to prepare a film-forming resin solution with a mass percentage of 1-75%. Prepare a flow battery separator on a conductive substrate by casting, extrusion or electrochemical deposition to form a film-substrate composite structure. Step (2): Add acidic or alkaline electrolyte to the modular or continuous membrane electrolysis cell; Step (3): Take out the membrane-substrate composite structure from step (1), ensuring that the membrane surface is undamaged, and immerse it in the electrolyte described in step (2); Step (4): A counter electrode is placed above or below the membrane-substrate composite structure in step (3), and the counter electrode is completely immersed in the electrolyte; Step (5): Apply current to the membrane-substrate composite structure and the counter electrode in step (4) to carry out the electrolysis process. Stir the electrolyte during electrolysis until sufficient small bubbles are generated between the membrane and the substrate or the substrate is completely corroded. Step (6): If the substrate in step (5) is not completely corroded but there are enough small bubbles between the membrane and the substrate, the membrane-substrate composite structure is removed, the membrane edge is peeled off and the interface is rinsed to separate the diaphragm; if the substrate in step (5) is completely corroded, the diaphragm is collected; if the number of small bubbles generated between the membrane and the substrate is insufficient, or the substrate is not completely corroded, resulting in insufficient peeling, the electrolysis is repeated to extend the electrolysis time.

2. The method for non-destructively peeling off the separator of a flow battery using electrolysis technology according to claim 1, characterized in that, In step (1), the film-forming resin is one or more of the following: perfluorosulfonic acid resin, sulfonated polyether ether ketone, polybenzothiazole, polybenzimidazole, sulfonated polyethylene, polyether sulfone, sulfonated polypropylene, polyimide, polysulfone, polyether ether ketone, perfluorocarboxylic acid resin, polyvinylidene fluoride resin, polypropylene, polyethylene, and polyvinylidene fluoride. The organic solvent is selected from one or more of the following: dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, or dichloromethane.

3. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, In step (1), the conductive substrate is one of the following: boron-doped diamond film, titanium-based ruthenium-iridium plate or foil, titanium-based iridium-tantalum plate or foil, titanium-based ruthenium-indium-tin plate or foil, titanium-based tin-antimony oxide plate or foil, titanium-based titanium suboxide plate or foil, and titanium-based lead dioxide plate or foil; at least one of the following: stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, niobium, tantalum, zirconium, tungsten, cerium, aluminum, bismuth, rhenium, barium, osmium, tin, lead, gold, silver, platinum, palladium, iridium, rhodium, molybdenum, and ruthenium metal material plate or foil; or any one of the following: graphite felt, carbon felt, graphite, glassy carbon, boron-doped diamond, activated carbon, graphene, carbon fiber, carbon nanotube, and carbon sponge carbon material plate or foil.

4. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, In step (2), the concentration of the acidic electrolyte is 0.1-5 mol·L⁻¹. -1 This includes solutions of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, carbonic acid, hydrosulfuric acid, sulfurous acid, hydrofluoric acid, or citric acid; the alkaline electrolyte concentration is 0.1-5 mol·L⁻¹. -1 This includes solutions of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ammonia, calcium hydroxide, sodium phosphate, sodium sulfite, sodium sulfide, or sodium aluminate.

5. The method for non-destructively peeling off the separator of a flow battery using electrolysis technology according to claim 1, characterized in that, In step (4), the counter electrode is in the shape of a sheet, rod, or foil, with a thickness of 5-100,000 μm. The counter electrode shape is any one of sheet, rod, filament, granular, sponge, mesh, and porous structure. The counter electrode material is one of boron-doped diamond film, titanium-based ruthenium-iridium plate or foil, titanium-based iridium-tantalum plate or foil, titanium-based ruthenium-indium-tin material or foil, titanium-based tin-antimony oxide plate or foil, titanium-based titanium suboxide plate or foil, and titanium-based lead dioxide plate or foil. At least one of the following metal material plates or foils: stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, niobium, tantalum, zirconium, tungsten, cerium, aluminum, bismuth, rhenium, barium, osmium, tin, lead, gold, silver, platinum, palladium, iridium, rhodium, molybdenum, and ruthenium. Any one of the following carbon material plates or foils: graphite felt, carbon felt, graphite, glassy carbon, boron-doped diamond, activated carbon, graphene, carbon fiber, carbon nanotube, and carbon sponge.

6. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, In step (4), the area ratio of the membrane-substrate composite structure to the counter electrode is 1:10 to 10:1, and the spacing is 1 mm to 100 mm; the membrane-substrate composite structure serves as the positive or negative electrode, and the counter electrode serves as the negative or positive electrode.

7. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, In step (5), when the electrolysis is performed in constant current mode, the current density range is 10 mA·cm⁻¹. -2 ~1000 mA·cm -2 The electrolysis time is 1–120 min, and the temperature is 25 ℃–70 ℃. In constant voltage mode, the voltage range is 1 V–150 V, the electrolysis time is 1–120 min, and the electrolysis temperature is 25 ℃–70 ℃. In constant current pulse mode, the current density range is 10 mA·cm⁻¹. -2 ~1000 mA·cm -2 The electrolysis time is 1–120 min, the frequency is 200–2000 Hz, the duty cycle is 20%–80%, and the electrolysis temperature is 25 ℃–70 ℃.

8. The method for non-destructively removing the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, The removed flow battery separator has a thickness of 10–100 μm, a tensile strength greater than 20 MPa, an elongation at break greater than 90%, and an ionic conductivity greater than 12 mS·cm. -1 .

9. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, Applicable flow battery systems include any one or more of the following: iron-chromium, vanadium-based, zinc-iron, ferro-based, zinc-bromine, sodium / bromine polysulfide, titanium-manganese, or organic flow batteries.

10. The method for non-destructively peeling off the separator for a flow battery using electrolysis technology according to claim 1, characterized in that, The surface of the removed diaphragm showed no mechanical damage, and the vanadium ion permeability constant was less than 20 × 10⁻⁶. -7 cm·min, and at 200 mA·cm -2 The energy efficiency of the flow battery is greater than 75% at the current density.